L’ixeutique, un exemple de gestion empirique de la biodiversité végétale par la communauté traditionnelle Tsaaya du massif du Chaillu, Congo - Victor Kimpouni; Jean Pierre Makita-Madzou; Ernest Apani; Marcel Motom (Revue d'ethnoécologie)
The traditional societies and especially their knowledge interested more than one anthropologist, in particular those of the first ages. In spite as of authorized efforts, the endogenous and empirical knowledge of the populations qualified of primitives, the field of the people and his environment studies still holds secrecies for us. The object of this study is to highlight the knowledge of the Tsaaya community of Chaillu through the ixeutic. Secular practice all over the world, the ixeutic of Tsaaya is made conspicuous by the (i) technical known ones nowhere elsewhere of cold transformation of latex into lime, (ii) the product conservation for the future hunting parties and (iii) the manufacturing of instrument of hunting like the bird calls. This ethnobotanic study brings information on (i) the plant species implied in the ixeutic one, (ii) the birds often limed and (iii) the mechanisms of collection of the products, and (iv) the hunting types. It brings out 15 spontaneous species and approximately about thirty birds species. As for the bird calls, several species of Sapotaceae which one extracts the almond of seeds are listed. At the ecological level and conservation of the vegetable biodiversity, the harvest techniques and lime conservation are described and analyzed. The Tsaaya ixeutic is an example of management of the biodiversity. It falls under the valorization of the Tsaaya knowledge related on ixeutic and the durable management of floristic diversity.